Photovoice Activities to Teach Writing for High School Students - Enti Khoirun Nisa (Borneo Educational Journal (Borju), 2021)
Photovoice is reflective learning that engages learners' writing ability by having their literature from their experiences into perspective through photography. It is reflected in what happened, what has been done, or what is happening. The central premise of the study is that students have difficulty expressing their perspectives and creativity in literature. They are unable to brainstorm successfully in an online classroom because of individual factors. Photovoice is a relevant tool to engage students' motivation and writing ability since the photovoice role as guidance to write literature review by gathering ideas by their perspective and reflecting their voice to divide with others. Thus, this study aims to report that investigated photovoice activity to teach writing to high school students. The research was conducted in one of the Senior High schools in Yogyakarta. The data collected through photovoice and analyzed by using SHOWeD Analysis (1) what do you see here; (2) What is happening; (3) how does this relate to our lives; (4) why are things this way; (5) how could this image educate people?